2008
DOI: 10.2116/analsci.24.543
|View full text |Cite
|
Sign up to set email alerts
|

pH-Potentiometirc Study of Polyion Complexes between Chitosan and Poly(vinyl sulfate) or Dodecylbenzene Sulfonate

Abstract: Polyion complexes of three chitosans with poly(vinyl sulfate) (PVS) and dodecylbenzene sulfonate (DBS) were examined by a potentiometric study that was to separately measure the pH of sample solutions individually prepared. Apparent formation constants (Ki) of ion association between the protonated amines of chitosan and the sulfates of PVS or the sulfonates of DBS were determined. The effects of pH, coexistent salt concentration, and molecular weight on the values of Ki were investigated in order to reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The apparent pKa decreased with the degree of dissociation (˛), particularly at low salt concentration. A calculation from the˛dependence of the pKa for COS (apparent pKa > 6 at˛= 0.8 in 1.5 mM NaCl solution) indicates that COS amine groups should be almost completely protonated at pH < 4 [18]. In this study, we observed equal electromigration at pH 3.0 and at pH 3.5, indicating that COS is completely dissociated at this low pH.…”
Section: Separation Of Cossupporting
confidence: 48%
See 1 more Smart Citation
“…The apparent pKa decreased with the degree of dissociation (˛), particularly at low salt concentration. A calculation from the˛dependence of the pKa for COS (apparent pKa > 6 at˛= 0.8 in 1.5 mM NaCl solution) indicates that COS amine groups should be almost completely protonated at pH < 4 [18]. In this study, we observed equal electromigration at pH 3.0 and at pH 3.5, indicating that COS is completely dissociated at this low pH.…”
Section: Separation Of Cossupporting
confidence: 48%
“…The dissociation constant (Ka) for chitosan amines depends on its molecular weight. We reported apparent Ka for C1, COS, and largemolecular-weight chitosans [18], and also estimated the effect of salt concentration. The apparent pKa decreased with the degree of dissociation (˛), particularly at low salt concentration.…”
Section: Separation Of Cosmentioning
confidence: 99%
“…The principle is based on formation of an ion-association complex between cationic polyelectrolyte and anionic polyelectrolyte. As the ion associate is mainly formed due to electrostatic interaction, the increase in concentration of a salt in a sample solution affects the stability constants of a colloidal titration reaction (Hattori and Katai 2008). However, the potentiometric method is inevitably accompanied by a reference electrode, which leaks a salt to a sample solution to some extent (Hattori et al 2010).…”
Section: Photometric Colloidal Titration Of Phmb-hcl With Crystal Viomentioning
confidence: 99%
“…In colloidal titration, a great amount of coexisting inorganic electrolytes often leads to titration errors (Senjyu 1969) because the increase in the concentration of a salt affects the stability constants of a colloidal titration reaction (Hattori and Katai 2008). Therefore, the effect of electrolytes (NaCl and CaCl 2 ) on the sharpness of the end point detection of PHMB-HCl was examined.…”
Section: Photometric Colloidal Titration Of Phmb-hcl With Crystal Viomentioning
confidence: 99%
“…Since the ion associate is mainly formed due to an electrostatic interaction, an increase in the concentration of a salt in a sample solution affects the stability constants of the colloidal titration reaction. 14 However, the potentiometric method is inevitably accompanied by a reference electrode, which leaks a salt to a sample solution to some extent. 15 As a result, the leaked salt affects the stability constants of the colloidal titration reaction, which leads to titration errors.…”
Section: Introductionmentioning
confidence: 99%